Analysis of Factors Affecting Motivation of Teachers Towards Teaching; a Case Study of Public Schools Samanabad, Faisalabad - Mehwish Shaukat; Rana Muhammad Amir; Hafiz Ali Raza (Asian Journal of Management, Entrepreneurship and Social Science, 2021)
Motivation plays a vital role in teaching. It is an internal process which helps individual to achieve their goal. Especially a teacher who is considered a builder of the nation if not motivated towards this sacred profession can be a great loss to its individual development and society as well. There are many factors which can de-motivate the teachers from teaching as low salary packages, job dissatisfaction, stress, classroom environment. Lack of motivation can negatively affect the students’ learning and their academic achievements. The aim of this study is to explore the factors that motivate the teachers towards teaching through intrinsic and extrinsic motivation. The factors which affect the motivation of teachers measured in relation to the teaching at public schools. The public school teachers of Faisalabad was the population for this research. The research was quantitative in its nature. The population of the study was 159. A sample size of 113 respondents obtained by using survey software method available online at www.surveysystem.com with confidence level 95% and a confidence interval 5%. Proportionate sampling technique used for the selection of the sample. A well-structured questionnaires were formatted and distributed among the respondents for data collection. The data analyzed through Statistical Package for Social Sciences (SPSS). Low salary packages, pressure from administration can negatively affect the motivation of teachers towards teaching. For the better performance and satisfaction, government should motivate the teachers through intrinsic and extrinsic rewards.